Biodegradable plastic applications towards sustainability : A recent innovations in the green product - Taofeeq D., Moshood; Gusman, Nawanir; Fatimah, Mahmud; Fazeeda, Mohamad; Mohd Hanafiah, Ahmad; Airin, Abdul Ghani (Elsevier Ltd, 2022)
The purpose of this study is to investigate the contribution of biodegradable plastics to sustainability in a new and sustainable plastics economy, in which plastics perform their useful function without causing negative externalities. Biodegradable plastics are those that degrade naturally over time. With research carried out across three diverse sustainability principles using the triple bottom line method, a multi-disciplinary strategy is a one-of-a-kind approach (social attitudes, environmental consequences, and economic characteristics). Biodegradable plastics became the initial target, as the position of plastics in the plastics system would inevitably be diminished if it could not be established for biodegradable plastics that give equivalent or improved material properties in contrast with traditional plastics. Therefore, the purpose of this study is to look at the various motives that drive companies to produce biodegradable plastic products, as well as the factors that influence their long-term viability. As a result, the study found that the economic component was the most important element, followed by environmental effects and social attitudes. The research also discusses the variables that influence the adoption of biodegradable plastics, as well as a sustainable framework for improving biodegradable plastics’ long-term viability. The findings also assess the effectiveness of the suggested framework, which includes seventeen principles spread over three levels of sustainability. There are nine for the social dimension, eight for the economic dimension, and seven for the environmental dimension. This paper offers a comprehensive and efficient means of evaluating and finding optimal options for industries with biodegradable plastics.